Temperature-dependent permeability of the ligand shell of pbs quantum dots probed by electron transfer to benzoquinone - Aruda, Kenneth O. (2015)
This paper describes an increase in the yield of collisionally gated photoinduced electron transfer (electron transfer events per collision) from oleate-capped PbS quantum dots (QDs) to benzoquinone (BQ) with increasing temperature (from 0 to 50 °C), due to increased permeability of the oleate adlayer of the QDs to BQ. The same changes in intermolecular structure of the adlayer that increase its permeability to BQ also increase its permeability to the solvent, toluene, resulting in a decrease in viscous drag and an apparent increase in the diffusion coefficient of the QDs, as measured by diffusion-ordered spectroscopy (DOSY) NMR. Comparison of NMR and transient absorption spectra of QDs capped with flexible oleate with those capped with rigid methylthiolate provides evidence that the temperature dependence of the permeability of the oleate ligand shell is due to formation of transient gaps in the adlayer through conformational fluctuations of the ligands.